Impulse buying and variety seeking: Two faces of the same coin? Or, maybe not! - Sharma, Piyush; Sivakumaran, B. (2003)
Impulse buying (IB) and variety seeking (VS) are both classified as spontaneous hedonic purchase behaviors influenced by feelings rather than logical thinking (Baumgartner 2002). However, there is little empirical research into their similarities and differences. We address this gap by investigating the association of both these behaviors with relevant consumer traits (consumer impulsiveness, optimum stimulation level and self-monitoring) and situational factors (involvement, product type, time availability and mood).